Fundamental theorem of algebra - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2022)
The purpose of the article is to familiarize teachers and students with the fundamental theorem of algebra for real polynomials and its proof. Polynomials of small degrees are considered separately. It is showed how equations of the third and fourth degree can be solved. An algorithm for solving cubic equations is proposed.